Analysis of Moral Values in Serat Kalatidha and Its Relevance to Pancasila and Citizenship Education - Moh Novandi; Leckie Glenn (Education Specialist, 2025)
Analysis of Moral Values and Honesty in Kalatidha Fiber and its Relevance to Pancasila Education and Citizenship. Undergraduated thesis. Yogyakarta. Faculty of Teacher Training and Education, University of PGRI Yogyakarta, November 2022. A developed nation is a nation that thinks about the morals of its young generation. This is one of the messages contained in the Serat kalatidha. Serat Kalatidha, by Ranggawarsita, teaches philosophy, how to deal with and overcome the moral crisis of a nation. In addition to moral education, honesty is also closely related to the noble values ​​of Pancasila. The purpose of this study is to determine the relationship between moral values ​​and the character of honesty contained in Serat Kalathida and their relevance to Pancasila and Citizenship Education (PPKN). This research uses library research method. The data sources for this research are primary data which is kalatidha fiber and secondary data derived from observations from other sources related to primary sources. Data analysis carried out in this study is the idealistic method, contextualization, and criticism. The results of this study in the form of kalatidha fiber have a relationship with moral values ​​and the character of honesty. This is obtained from various messages conveyed by Raden Ngabehi Ranggawarsita in his works such as piwulang, religious, suggestions, and prohibitions. Meanwhile, the honesty values ​​contained in the Fiber Kalatidha are being aware and alert by sticking to the truth even though those around them are doing violent acts.